Forward Modeling of Infinitesimal Dipole Dipping Effects in Marine CSEM survey - Hussain , Nazabat (2011)
This paper present numerical modeling of infinitesimal dipole for the purpose of finding irregularities in real time survey data of marine controlled source electromagnetic survey. Algorithm for numerical solution using staggered grid scheme of finite difference method has been developed by using auxiliary potential functions in Helmholtz equation. Solution is obtained through a) discretized the solution region into number of elements and define boundary condition b) implementing algorithm for resulting system of linear algebraic equations. The results provides detailed understanding of irregularities in survey data caused by improper orientation of source during electromagnetic sounding for exploration of petroleum reserves in deep sea.